When Transparency Fails: Financial Incentives for Local Banking Agents in Indonesia - Deserranno, Erika; León-Ciliotta, Gianmarco; Witoelar, Firman (The Review of Economics and Statistics, 2025)
Abstract We study the effect of raising the level and transparency of financial incentives offered to local agents for acquiring clients of a new banking product on take-up. We find that paying agents higher incentives increases take-up and usage, but only when the incentives are unknown to prospective clients. When disclosed, higher incentives have no effect on take-up and usage, despite greater agent effort. This is due to the financial incentives sending a negative signal to potential clients about the reliability and trustworthiness of the product. Hence, when designing incentives, organizations should consider both their level and transparency.